Readability of Online Information on Celiac Disease: A Brief Report. Issue 2 (2nd April 2020) - Ethan, Danna; Meleo-Erwin, Zoe; Fera, Joseph; Garcia, Phillip; Basch, Corey H.
Abstract: Celiac disease (CD) is an autoimmune condition characterized by an intolerance to dietary gluten for those with a genetic predisposition. The Internet has become a key source of information about CD as well as a gluten-free diet (GFD), although the quality is varied. There has been little investigation into the readability of online CD information. Keyword "celiac disease" was used for a search in the browser, Google Chrome. URLs of the first 100 English websites were recorded; sponsored or advertised websites were not included in the sample. Five recommended tests generated by Readable.io were utilized to assess the sample's readability scores. Only one of the 100 websites received an acceptable reading score on two of the five reading assessments. Websites with extensions of .com or .org were equally likely to be written at the same unacceptable level. Informational websites on celiac disease may serve as an unintentional barrier for consumers seeking readable, online material on this health topic.